miR-10c Facilitates White Spot Syndrome Virus Infection by Targeting Toll3 in Litopenaeus vannemei - Zuo, Hongliang; Liu, Xinxin; Luo, Mengting; Yang, Linwei; Zhu, Zhiming; Weng, Shaoping; He, Jianguo; Xu, Xiaopeng (Frontiers in Immunology, 2021)
Toll-like Receptors (TLRs) are canonical cell membrane receptors essential for recognizing pathogens and inducing immune related-gene expression in Litopenaeus vannamei. It has been proved that Toll3 in L. vannamei (LvToll3) plays a critical role in antiviral immunity by inducing the transcription of interferon regulatory factor (IRF) which orchestrates shrimp antiviral responses similar to the interferon system of vertebrates. However, whether LvToll3 could activate the IRF cascade to defense the invasion of white spot syndrome virus (WSSV) in L. vannamei is remained unknown. In this study, a novel microRNA (miRNA) of miR-10 family, temporarily named as miR-10c, was first identified from L. vannamei. MiR-10c may play a nonnegligible regulatory role in shrimp immune responses since it was constitutively expressed in all detected tissues and transcriptionally induced by immune stimulation. Functional analysis validated that miR-10c could target LvToll3 and inhibit its expression, through which blocked the nuclear translocation of IRF and facilitated the infection of WSSV. To the best of our knowledge, the present study revealed the first report of a TLR targeted by miRNA in crustaceans and provided a solid evidence of LvToll3 inducing anti-viral immunity by activating IRF cascade in L. vannamei. These findings provide new insights into the participation of miRNA in the regulation of immune responses and contribute to the further understanding of the mechanisms of TLRs induced antiviral immunity in L. vannamei.